2022
DOI: 10.3390/ma15030793
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Action Mechanism of Titanium in Alumina–Magnesia Castables by Adding Different Ti-Bearing Compounds

Abstract: To investigate the action mechanism of titanium, the effects of different Ti-bearing compounds, including CaTiO3, MgTiO3, and nano-TiO2, on the properties of alumina–magnesia castables were studied. By analyzing the phase compositions, microstructures, and physical and mechanical properties of the castables, it was demonstrated that an intermediate product, CaTiO3, was first generated. This was then consumed by solid-solution reactions, and titanium was involved in the liquid formation as the temperature incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Tang et al [10] investigated the influence of CaTiO 3 , MgTiO 3 and nano-TiO 2 additions on the physical and mechanical properties of alumina-magnesia castables in order to increase castable densification, thus, inhibiting the effects of CA 6 and spinel expansion. They found that MgTiO 3 is unstable in all tested materials, while 2 wt.% CaTiO 3 results in the best castable properties.…”
Section: Castables and Bindersmentioning
confidence: 99%
“…Tang et al [10] investigated the influence of CaTiO 3 , MgTiO 3 and nano-TiO 2 additions on the physical and mechanical properties of alumina-magnesia castables in order to increase castable densification, thus, inhibiting the effects of CA 6 and spinel expansion. They found that MgTiO 3 is unstable in all tested materials, while 2 wt.% CaTiO 3 results in the best castable properties.…”
Section: Castables and Bindersmentioning
confidence: 99%